The Golden Age: Shining the Light on Theragnostics. Issue 8 (24th June 2021) - Yang, Yamin; Wang, Hongjun
Abstract : Gold nanoparticles have attracted unprecedented attention as one of the leading nanomaterials in the field of biomedicine. Of particular interest are their inherent and geometrically tunable optical properties upon the interaction with light, facilitating breakthroughs in light‐mediated diagnosis and therapeutics. Herein, an up‐to‐date overview of the current research in utilizing versatile gold‐based nanosystems with distinctive optical features for optical imaging and phototherapy is provided. The recent advances in optical biosensing, surface‐enhanced Raman scattering‐based detection, photoacoustic imaging, optical coherence tomography, photothermal therapy, light‐triggered drug release, photodynamic therapy, and optomodulation of neural functions using the novel and elegant gold nanostructures of unique design are summarized. In recognition of the burgeoning popularity of integrating multiple diagnostic and therapeutic functions in one system, recent developments of various multifunctional gold nanoplatforms for the light‐enabled concomitant diagnosis and therapy are also highlighted. In the end, the current limitations and perspectives in clinical translation of gold nanomaterial‐assisted photodiagnosis and phototherapy are discussed along with the concluding remarks. Abstract : The distinctive and geometrically tunable optical properties of gold nanostructures facilitate their unprecedented potentials in light‐mediated diagnosis and therapeutics. Herein, an up‐to‐date overview of the current research on utilizing versatile gold‐based nanosystems for optical imaging and phototherapy is provided, where multifunctional gold nanoplatforms for the light‐enabled concomitant diagnosis and therapy are highlighted.